Peran Pelayanan Apoteker terhadap Pengetahuan Swamedikasi Obat Bebas dan Bebas Terbatas di Apotek - M. Dwi Suprobo; Pamungkas Aji (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Self Medication is self treatment, starting from the onset of symtoms to the selection and use of medications. Pharmacists provide information to the public on drug selection for self medication to ensure appropriate treatment according to their needs. Providing self medication information is crucial for improving public knowledge. This study aims to increase pharmacists' awareness in providing it to the public and increase public knowledge when using over the counter and limited over the counter drugs in Larangan - Brebes area. A total of 100 respondents participated in this study which was conducted using an observational cohort design. Data collection was conducted using a prospective pre-test and post-test. The analysis used a non-parametric t-test using the Wilcoxon alternative test. The respondents’ educational status was dominated by high school graduates or equivalent, and 54 respondents visited the pharmacy less then five times per month. The results obtained from this study were p = 0.001 and the difference knowledge score was 11.22, with an average pre-test score of 27.54 and post-test 38.76. There were significant results on knowledge of self medication for over the counter and limited over the counter drugs after pharmacists provided services.